TEACHING ALPAHBET FOR NON NATIVE ENGLISH LEARNERS: A CASE STUDY OF FIRST GRADERS - Agnes Widyaningrum; Vinna Octavia (Dinamika Bahasa dan Budaya, 2019)
Non-native English learners need time to learn English language since they just heard without knowing how to pronounce it correctly. This condition occurs in common Primary Schools because the students do not have foreign language background, at school as well as at home. The hidden curriculum focusing on students’ soft skills are not well administered as the school managements think that what they have to do in running the academic atmosphere is teaching well for their students. The first step in teaching English for young learners especially those who are non-native English learners is introducing English by getting to know it. Piaget’s child’s development contributes in helping teachers to know their student’s growth physically and mentally in order to help them learn better while they play different teacher’s roles. Piaget proves that cognitivism gives insight that is children’s develop through stages since they were born. First graders at their age is on the stage called preoperational with one of characteristics that is language development with the goal to create symbolic thought. One way to achieve this goal is by teaching alphabet for first graders.